Mental health of international migrant workers amidst large-scale dormitory outbreaks of COVID-19: A population survey in Singapore - Young Ern Saw; Edina YQ Tan; P Buvanaswari; Kinjal Doshi; Jean CJ Liu (Elsevier, 2021)
Introduction: Worldwide, COVID-19 clusters have emerged within communities of international migrant workers operating in high-density work and living environments. Despite their increased vulnerability, no study has documented the mental health burden of COVID-19 amongst these groups. To address this gap, we conducted a survey of migrant workers involved in large-scale dormitory outbreaks within Singapore. Methods: Between 22 June to 11 October 2020, questionnaires were distributed to 1011 migrant workers undergoing extended movement restrictions. Mental health symptoms were measured using the 21-item Depression, Anxiety and Stress Scale (DASS-21). As covariates, we assessed participants' socio-demographics, quarantine status, COVID-19 health concerns, financial stability, and exposure to news and misinformation. Linear regression models were fitted to identify factors associated with DASS-21 scores. Results: Complete movement restrictions were associated with increased depression and stress symptoms, while being diagnosed with COVID-19 was associated with increased anxiety. Participants who harboured fears about their health or job, perceived their health to be poorer, or had greater exposure to COVID-19 rumours reported higher depression, anxiety, and stress levels. Across the cohort, rates of severe or extremely severe depression (3.1%, 95% CI: 2.1-4.3%), anxiety (4.1%, 95% CI: 2.9-5.5%), and stress (1.3%, 95% CI: 0.7-2.2%) were similar to those observed in the general population for the host country (Singapore). Conclusions: As the first mental health survey of low-waged migrant workers during the pandemic, our findings provide a basis to identify and support at-risk individuals. This is critical as migrant workers often have limited access to healthcare services. At the same time, we documented resilience within the cohort as a whole.